EFEKTIVITAS APLIKASI IPB MOBILE FOR STUDENT SEBAGAI PEMENUHAN KEBUTUHAN INFORMASI TENTANG KAMPUS BAGI MAHASISWA - Eka Rachmawati; Qoute Nuraini Cahyaningrum; Dwi Rini Sovia Firdaus (Jurnal Penelitian Sosial Ilmu Komunikasi, 2022)
This research aims to analyze the level of correlation between the effectiveness of the IPB Mobile for Student as the fulfillment of campus information needs for students. This research consisted of variable X namely, program success, the success of the intended, satisfication the program, level of output and input and achieving the overall objective and variable Y namely perception of the problem by user, intent for use of the information by user, internal knowledge state of the user in respect to the problem at hand, and public knowledge expectations or estimate by the user. This study uses descriptive quantitative research. Theory used in this study is Uses and Gratification theory. This study was distributing questionnaires to 101 students of IPB University. The method used to test correlation uses the Spearman Rank formula, data processing is assisted with SPSS version 25. The result of this research is theres a significance level of .000 and a correlation of .760 **. This means that there is a correlation between the two variables with a positive direction so that the higher the effectiveness of applications the higher the fulfillment of information needs for students.